Curriculum Dynamics in Colleges of Education: Interactions between Intended, Translated and Achieved Curricula - Mustapha, Abiodun Gafar; Owolabi, Tunde; Jolaoluwa, Grace; Adigu, Hamed; Salami, Sahda (FKIP - Universitas Riau, 2025)
This study investigates the interactions between intended, translated and achieved curricula in colleges of education in Lagos State, Nigeria. Employing a descriptive survey research design, the study collected data from a sample of 180 randomly selected science students across three purposively chosen tertiary institutions within the state. The Intended, Translated, and Achieved Curriculum and Student Academic Achievement Questionnaire (ITACSAAQ) was developed to gather insights into students’ perceptions regarding the curricula's impact on their performance. The questionnaire comprised demographic information and items rated on a 4-point Likert scale. Validation by experts in curriculum studies ensured the instrument's reliability, yielding a Cronbach's Alpha score of 0.73. Data analysis involved mean, standard deviation and analysis of variance. Findings revealed statistical significant impact of intended curriculum and the implemented curriculum F(13, 15) = 2.44, p>0.02), however, no statistical significant impact of translated curriculum on achieved F(13, 15) = 1.11; p >0.05. The study concludes that this type of comprehensive approach is crucial for fostering meaningful academic achievement and ensuring the effectiveness of science education in Nigeria. The study recommends that educational stakeholders should ensure that the intended curriculum is regularly reviewed and updated to reflect current academic, societal, and industry demands.